Notes on the typification of Ochagavia litoralis (Bromelioideae, Bromeliaceae) - Schneider, Julio V.; Zizka, Georg; Muñoz-Schick, Melica (Phytotaxa, 2012)
Ochagavia Philippi (1856: 168) is a small genus of the Bromelioideae (Bromeliaceae) and contains four species endemic to Chile according to the most recent revision by Zizka et al. (2002). The species are attractive plants and some were introduced early into cultivation and became naturalized in north-western Europe.